Sb doping and Sb2O3 coating collaboration to improve the electrochemical performance of LiNi0.5Mn0.5O2 cathode material for lithium ion batteries. (20th December 2020) - Hu, Guorong; Shi, You; Fan, Ju; Cao, Yanbing; Peng, Zhongdong; Zhang, Yinjia; Zhu, Fangjun; Sun, Qian; Xue, Zhichen; Liu, Yanhua; Du, Ke
Abstract: LiNi0.5 Mn0.5 O2 suffers from surface structure instability and capacity degradation upon cycling, and single doping or coating cannot effectively solve the problem. In this work, the Sb-modified LiNi0.5 Mn0.5 O2 is successfully prepared by solid-state reaction process at high temperature, which simultaneously realizes Sb doping and Sb2 O3 coating. Electrochemical experiments show that the Sb-modified LiNi0.5 Mn0.5 O2 material has enhanced electrochemical performance. The capacity retention of the Sb-modified LiNi0.5 Mn0.5 O2 material is 81.00% at 1.0 C after 250 cycles, while it is 59.08% for the bare sample, and performs 105.7 mAh g −1 at 5 C compared to 76.6 mAh g −1 for the bare sample. Therefore, Sb doping and Sb2 O3 coating collaboration are beneficial to enhance electrochemical performance. This effective design strategy can be used to improve the electrochemical performance of other layered cathode materials.